2016
DOI: 10.1074/mcp.m115.054510
|View full text |Cite
|
Sign up to set email alerts
|

Pathology Tissue-quantitative Mass Spectrometry Analysis to Profile Histone Post-translational Modification Patterns in Patient Samples

Abstract: Histone post-translational modifications (hPTMs) generate a complex combinatorial code that has been implicated with various pathologies, including cancer. Dissecting such a code in physiological and diseased states may be exploited for epigenetic biomarker discovery, but hPTM analysis in clinical samples has been hindered by technical limitations. Here, we developed a method (PAThology tissue analysis of Histones by Mass Spectrometry - PAT-H-MS) that allows to perform a comprehensive, unbiased and quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 33 publications
4
64
0
Order By: Relevance
“…Recently, our group has developed a series of histone enrichment methods that allow the MS-based analysis of histones from patient-derived samples, including primary cells, frozen tissues, and formalin-fixed paraffin-embedded (FFPE) tissues. [9][10][11] Among them, the pathology tissue analysis of histones by mass spectrometry (PAT-H-MS) method allowed for the first time a comprehensive MS-based profiling of epigenetic marks in patient pathology tissues. We employed these different approaches to study histone H3 methylation and acetylation patterns in breast cancer subtypes, [12] and to investigate histone PTM changes in the transition from primary tumors to culture conditions and xenograft models.…”
Section: Doi: 101002/prca201700166mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our group has developed a series of histone enrichment methods that allow the MS-based analysis of histones from patient-derived samples, including primary cells, frozen tissues, and formalin-fixed paraffin-embedded (FFPE) tissues. [9][10][11] Among them, the pathology tissue analysis of histones by mass spectrometry (PAT-H-MS) method allowed for the first time a comprehensive MS-based profiling of epigenetic marks in patient pathology tissues. We employed these different approaches to study histone H3 methylation and acetylation patterns in breast cancer subtypes, [12] and to investigate histone PTM changes in the transition from primary tumors to culture conditions and xenograft models.…”
Section: Doi: 101002/prca201700166mentioning
confidence: 99%
“…We have previously shown that while FFPE storage is suitable for the MS analysis of at least 24 differentially modified histone H3 peptides, it causes the appearance/increase of artifactual methylations on specific residues, which therefore cannot be reliably quantified. [11] By exploiting the C18 StageTip column enrichment, which is compatible with an in-solution digestion that allows thoroughly dissecting histone H4 tail acetylations and K20 methylations, we aimed at verifying whether relative differences in histone H4 PTMs can be quantified in FFPE samples. We therefore applied an Arg-C digestion following C18 StageTip column enrichment to four ovarian cancer samples that were stored either as FFPE or fresh-frozen tissues, which were used as a reference (Table S1, Supporting Information).…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Despite immense efforts, there is still a need to further develop protocols for sample processing towards downstream proteomics analysis. In spite of these limitations, recent methodological developments have facilitated quantitative analyses by parallel reaction monitoring on FFPE breast cancer tissues [21] and PTM detection [22,23]. For a complete review of the proteomic developments in the analysis of FFPE tissues we refer to [24].…”
Section: Collection and Treatment Of Brain Samplesmentioning
confidence: 99%
“…heating, there are still irreversible modifications with formaldehyde present. It has been shown recently that formylation and methylation on lysine are common modifications in FFPE tissue samples(46)(47)(48). However, these modifications are rarely included in the database search in studies using FFPE material.…”
mentioning
confidence: 99%